The Effect of Competence-Building Narrative on Chinese Adolescents’ Persistence - He W; Ming Z; Huang L; Chen T (Psychology Research and Behavior Management, 2023)
Wuming He,1,2 Zhu Ming,1,2 Lulu Huang,2,3 Tiancai Chen4 1Guangdong Provincial Key Laboratory of Development and Education for Special Needs Children, Zhanjiang City, Guangdong Province, People’s Republic of China; 2School of Education Science, Lingnan Normal University, Zhanjiang City, Guangdong Province, People’s Republic of China; 3Xinyi No.2 High School of Guangdong, Xinyi City, Guangdong Province, People’s Republic of China; 4Zhanjiang Aizhou Middle School, Zhanjiang City, Guangdong Province, People’s Republic of ChinaCorrespondence: Zhu Ming, Email mzzhj2018@163.comAbstract: Persistence is one of the most critical aspects of learning motivation, but little attention has been paid to persistence intervention in the literature. The current study took a perspective from narrative psychology to examine the effect of narrative form on junior middle school students’ ability to persist. Thirty-two students were randomly assigned to the experimental group of competence-building narrative and the control group. While all the students constructed past experiences of success and failure, those in the experimental group were prompted to think from a competence-building perspective. Then both groups solved a figure-based problem, within which the researcher recorded their number of attempts and time spent. Results showed that those who construct past success and failure from a competence-building perspective attempted more times and spent more time on the unsolvable problem.Keywords: narrative psychology, persistence, narrative intervention, adolescents, motivation